Halfway House: Prisoner Reentry and the Shadow of Carceral Care - Martin, Liam (Alternative Criminology, 2021)
Frontmatter -- Contents -- 1. Carceral Care -- 2. A Blessing in Disguise -- 3. Halfway Home -- 4. Bridge Is Family -- 5. The Recovery Hustle -- 6. The Drug Crisis Outside the Door -- 7. No Narcotics -- 8. Leaving Bridge House -- 9. Alternatives -- Acknowledgments -- Notes -- References -- Index -- About the Author